Cyberformance and Children’s Theatre: a Contextual Examination of the Janelle and Joella Paradigm - Gana, Emmanuel Tsadu (Universitas Negeri Surabaya, 2024)
This article identifies cyberspace as an alternate theatre environment for audiences to see performances. There is no doubt that the internet has had a tremendous influence on human society; the interconnectedness and easy access to information and resources which it enables is a testament to this. Theatre artists have recently tapped into cyberspace to create content for an expanding online audience. This article explores how performance can enhance children's theatre in this digital space. It examines the concept of children’s theatre and defines children-centered online content as performance. The article broadens the definition of